Law and the stranger - Sarat, Austin; Douglas, Lawrence; Umphrey, Martha Merrill (Stanford, Calif. : Stanford Law, 2010)
Law calls communities into being and constitutes the 'we' it governs. This act of defining produces an outside as well as an inside, a border whose crossing is guarded, maintaining the identity, coherence, and integrity of the space and people within. Those wishing to enter must negotiate a complex terrain of defensive mechanisms, expectations, assumptions, and legal proscriptions. Essentially, law enforces the boundary between inside and outside in both physical and epistemological ways. This book explores the ways law identifies and responds to strangers within and across borders.
Specialized.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Aliens; Emigration and immigration law -- Philosophy; Law -- Philosophy; Sociological jurisprudence; Law; Jurisprudence & general issues; Methods, theory & philosophy of law; Laws of specific jurisdictions & specific areas of law